The Fall of the Tektōn and The Rise of the Architect On The Greek Origins of Architectural Craftsmanship - Holst, Jonas (2017)
The origins of architectural craftsmanship in ancient Greece are to be found in the archaic arts of tectonics. The first Greek architects, appearing under that name around the 6th century BC, rose out of and based their work on this age-old tectonic tradition, which semantically underwent a transformation during the time from Homer to Plato, the latter relegating the tektones to a lower rank in the order of craftsmanship. Through a detailed reading of the ancient Greek testimonies of the tectonic tradition, the paper demonstrates that in the Homeric tradition the tektones were hailed as versatile, first-rate craftsmen who created wonders out of matter, but in classical times they fell from their high status of old. In Plato’s writings tectonics ends up at the lower end of the epistemological and ontological scale.
Keywords: Tectonics, Homer, craftsmanship, Daedalus, architect, Plato.